Trade, wages, and productivity - Kristian Behrens; Giordano Mion; Yasusada Murata; Jens Suedekum (Center for Economic Studies and ifo Institute (CESifo), 2012)
We develop a new general equilibrium monopolistic competition model with variable demand elasticity, heterogeneous firms, and multiple asymmetric regions. Wages, productivity, consumption diversity, and markups across firms and markets are all endogenously determined and respond to trade integration in a way that is consistent with empirical evidence. Using Canada-US regional data, we structurally estimate the model and simulate the impacts of removing all trade barriers generated by the Canada-US border. We find that Canadian average labor productivity increases by 8.03%, whereas US average labor productivity rises by just 1.02%. Consumers' exposure to market power falls sizably by up to 12.11% in the Canadian provinces, and by up to 2.82% in the US states. At the firm level, however, markup changes are ambiguous and depend on the firm's productivity and location. Our results suggest that markups on the firms' side provide a very different piece of information than markups on the consumers' side, which are central to any welfare statement.
Keywords: F12; F15; F17; 330; firm heterogeneity; endogenous markups; gravity equation; monopolistic competition; general equilibrium